Evaluating a college student's urethritis. Issue 7 (16th July 2016) - Donato, Annemarie Sipkes; Durham, Catherine; Conner, Ruth
Abstract : Abstract: Gonorrhea is the second most common sexually transmitted infection (STI) after chlamydia. After a significant decrease from 1975 to 2009, trends reveal that gonorrhea is on the rise. NPs need to review the latest CDC guidelines regarding STIs, as treatment guidelines are regularly changing.